PENERAPAN MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN MATEMATIKA MATERI STATISTIKA - Angelinus Aurolio Pelealu; Cori Pitoy; Anneke Pesik (ADIBA : JOURNAL OF EDUCATION, 2022)
The purpose of this study is to see the difference in the average learning outcomes of mathematics in statistics materials using the Problem Based Learning learning model and the direct learning model. The type of research used is pseudo-experimentation. The research design used is The Matching Only Posttest Control Group Design. The sample consisted of 2 normal and homogeneous classes determined through lottery, class VIII A totaled 16 students as an experimental class and class VIII B totaled 16 students as a control class located at Rurukan Christian Junior High School in Tomohon city. The average statistical learning outcomes of experimental class students were 83.63 and the average learning outcomes of control class students were 78.44. The study statistics used a t-test with tcount = 3.44 > ttable = 1.69 with a real level of α = 0.05. It is concluded that the average learning outcomes using the Problem Based Learning learning model are more than the average learning outcomes using the direct learning model.